THE ANALYSIS OF FIGURATIVE LANGUAGE USED IN THE LYRIC OF BRUNO MARS’S SONGS - Megazain, Hamim; Sulistyanto, Irwan (Jurnal Pendidikan Bahasa Inggris Proficiency, 2022)
Language is tool of human beings to communicate each other. People can express their ideas, thought, and feelings through language. One of the ways to learn language is by used song. According to Apsari (2012), by using songs the students tend to be more active in the teaching and learning process. It showed that people can learn English through song. Actually, in fact so many people do not really understand about figurative language, how to classify the type and explain the denotative meaning each figurative meaning. The research design used in this research is descriptive qualitative method. The unit analysis of research is the figurative languages, contextual, connotative, denotative meaning, and the dominant of figurative which are found in the song lyric of Bruno Mars’s songs. The researcher chose five songs in the album Doo-Woops & Hooligans. The songs were Grenade, Just the way you are, marry you, Talking to the Moon, and Count on Me. In doing analysis, the researcher used identification, classification, and analysis. The result of the analysis showed that the types of figurative language in the five songs are metaphor, repetition, paradox, symbol, hyperbole, allegory, apostrophe, simile, and synecdoche. In the five songs that have been selected, the dominant of figurative language is repetition. The contextual meanings of figurative language were different from connotative meaning